CHEMICAL AND MICRO-COMPOSITION PRODUCTION OF ORGONOMINERAL (ALZ) LOW GRAVEL CONCRETE MIXTURE (American Journal of Interdisciplinary Research and Development, 2025)
The article is based on the chemical and microstructural formation of a low-gravel concrete mixture using organomineral additives, and the determination of the specific negative effects of additives in the contact zone of fillers as a result of the formation of a concrete composition.